Zinc as a central modulator of heat stress-induced intestinal and systemic dysfunction in poultry - Erek, Gozde; Uulu, Nursultan Arapbai; Sahin, Kazim (Pergamon-Elsevier Science Ltd, 2026)
Heat stress (HS) is a major environmental challenge in modern poultry production, where high metabolic heat output and intensive genetic selection increase vulnerability to thermal load. Beyond impairing thermoregulation and feed intake, HS disrupts intestinal barrier integrity, induces oxidative stress and inflammation, and promotes systemic metabolic dysregulation. The gastrointestinal tract has therefore emerged as a central target and amplifier of HS-induced pathology, highlighting the importance of gut-focused nutritional interventions. Zinc (Zn), an essential trace element with broad catalytic and regulatory functions, has gained attention as a key modulator of intestinal and systemic resilience under HS conditions. Accumulating evidence indicates that Zn not only supports antioxidant defenses and immune regulation but also preserves epithelial architecture by stabilizing tight junctions (TJ), modulating heat shock responses, suppressing inflammatory signaling, and promoting epithelial renewal. At the molecular level, Zn acts as a signaling ion through activation of the Zn-sensing receptor, G protein-coupled receptor 39 (GPR39) and downstream phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) and mitogen-activated protein kinase (MAPK) pathways, thereby facilitating epithelial repair and barrier restoration. Recent avian intestinal organoid studies provide direct mechanistic evidence that organic and moderately chelated Zn sources, such as Zn proteinate, more effectively alleviate HS-induced epithelial injury than inorganic forms. Complementary in vivo data further demonstrate HS-induced redistribution of Zn via coordinated regulation of Zn transporters and metallothionein, linking local intestinal protection with systemic Zn homeostasis. In conclusion, current evidence positions Zn as a central nutritional regulator of HS resilience and supports the development of precision Zn supplementation strategies for sustainable poultry production under increasing thermal stress.
Keywords: Heat Stress; Zinc; Intestinal Barrier Integrity; Gut Health; Oxidative Stress; Inflammation; Tight Junctions